Mosquito diversity across altitudinal and land-use gradients in tropical Indonesia - RISKI ANDRIAN JASMI; ENGGAR HIDAYAT; MUHAMMAD FARHAN KURNIA (Society for Indonesian Biodiversity, 2026)
Abstract. Jasmi RA, Hidayat E, Kurnia MF. 2026. Mosquito diversity across altitudinal and land-use gradients in tropical Indonesia. Biodiversitas 27 (2): d270227. https://doi.org/10.13057/biodiv/d270227. Altitudinal variation is an important environmental factor influencing the distribution and dynamics of vector insect communities in tropical regions. However, information on how elevational gradients affect mosquito distribution and diversity in Banten Province remains limited. This study aimed to examine the association between elevation and key environmental factors in shaping mosquito diversity. Sampling was conducted at 13 sites (n = 13) across an elevational range of 12-815 masl. Mosquitoes were collected between 18:00 and 06:00 WIB (UTC+07:00). Environmental parameters recorded included air temperature, relative humidity, land-use category, vegetation, and the availability of aquatic habitats. Relationships between elevation, temperature, and humidity with abundance were analyzed using Spearman correlation. Differences in diversity among elevational zones were tested using the Kruskal-Wallis test, followed by Dunn's post hoc test. A total of 3,528 mosquitoes representing nine species and five genera were collected. Total mosquito abundance declined sharply with increasing elevation and was strongly negatively correlated with elevation (r = -0.93, p<0.001) but positively correlated with air temperature (r = 0.77, p = 0.02). Culex quinquefasciatus (79.13%) and Culex vishnui (19.27%) dominated lowland areas, whereas Armigeres subalbatus showed increased abundance at higher elevations. Species richness remained relatively stable along the elevational gradient (2-4 species), indicating that elevation primarily influenced species dominance and abundance distribution rather than the number of species present. These findings suggest that elevation is strongly associated with mosquito diversity. Based on vector abundance and composition, potential transmission risk may be higher in lowland areas; however, pathogen prevalence was not assessed in this study. Because the study was observational, with possible collinearity between elevation and temperature and limited high-elevation replication, causal interpretations should be made cautiously.